IMPLEMENTATION OF ISLAMIC EDUCATION CURRICULUM PRINCIPLES AT STATE ISLAMIC ELEMENTARY SCHOOL - Okni Aisa Mutiara; Idi Warsah; Amrullah Amrullah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Initial guideline of learning is the curriculum principles used to create clear, correct and detailed academic direction. This research aims to find out how state Islamic elemnatary school (MIN) 01 Rejang Lebong implements its principles of the Islamic education curriculum by using a qualitative approach. Data were collected using interview, observation, and documentation techniques and analyzed using three , namely data reduction, data presentation, and conclusion. In conclusion, the implementation of the Islamic education curriculum principles at MIN 01 Rejang Lebong has been carried out affluent with various strategies used, ranging from lesson plan, learning method adapted to the learning material, and then the learning application used formal, informal and social learning. The supporting factor is that the religiosity has been embedded in the student’s character, it is not fixated on the formal learning process. Inhibiting factors are laziness, naughtiness, disobey the rules, and anti-social character of children.